Pleomorphic Adenomas Recurrences Within the Parapharyngeal Space - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
This study was undertaken to evaluate and concentrate on the recurrent pleomorphic adenomas (PAs) of the parapharyngeal space. The records of 9 patients treated for recurrent PAs occupying parapharyngeal space were retrospectively reviewed. The study population comprised 6 women and 3 men with a mean age of 51 (range, 35-79 years). Before the first revision surgery, imaging studies and clinical examinations showed 1 solitary mass in 4 patients, 2 solitary masses in 3 patients, and 3 or more masses in 2 patients. After first revision surgery, 4 patients had rerecurrences with multinodular disease. Two of 4 patients underwent radiation therapy (RT), and the other 2 patients underwent second revision surgery, among whom 1 patient underwent third revision surgery, and the other one was also submitted to RT. Overall, 12 reoperations were performed, and at the end of all operations, 4 patients had rerecurrences and residual disease. In conclusion, we recommend RT to patients with multinodular disease, known tumor spillage, and residual tumor in addition to revision surgery. Histopathologic features, surgical resection, relationship to surrounding vital tissues, and postoperative adjuvant radiotherapy are the most important determinants for recurrent PAs.
Keywords: Recurrent pleomorphic adenoma; parapharyngeal space; salivary gland; PAROTID-GLAND; SALIVARY-GLAND; MANAGEMENT; SURGERY; EXPERIENCE; NEOPLASMS; RUPTURE; TUMORS